Management Framework for Quality Assurance to Strengthen Technology and TVET Pre-service Teacher Education - Cabreros, Bryan; Barbacena, Cherrypyn (Journal of Technical Education and Training, 2024)
This study developed a management framework for quality assurance to enhance Technical-Vocational Education and Training (TVET) and technology pre-service teacher education programs in CALABARZON (Cavite, Laguna, Batangas, Rizal, and Quezon). Using the three-round Delphi consensus-building technique, the research assessed quality assurance practices and challenges in managing Bachelor of Technology and Livelihood Education (BTLEd) and Bachelor of Technical Vocational Teacher Education (BTVTEd) programs. The study also examined key factors affecting student performance in licensure examinations, career decision influences, and strategies to improve program appeal. Thirteen Delphi experts, including College Deans and program chairs, and 117 BTLEd and BTVTEd graduates participated. Thematic and statistical analyses, including the Mann-Whitney U test, compared assessment differences between graduates concerning licensure exam performance, career decisions, and program appeal strategies. The findings highlight that Teacher Education Institutions (TEIs) in the region prioritize quality assurance through curriculum reviews, faculty engagement, accreditation, facility maintenance, and continuous improvement. However, they face challenges such as resource limitations, curriculum misalignment, faculty development issues, and lack of specific quality assurance standards for TVET programs. Graduates noted factors influencing their licensure exam performance and career decisions, emphasizing the importance of review preparation, teaching strategies, and professional development. To enhance program appeal, there is a need for sustained career guidance, institutional initiatives, and program awareness efforts. The study recommends strengthening collaboration with stakeholders and implementing the proposed management framework to align with national and international standards.